The Context of Discourse in the Novel Heartbreak Motel by Ika Natassa Published in 2022 - Palupi, Muji Endah; Andayani, Endang Sri; Dhini, Ulfa Rahma (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research aims to determine the context of discourse in the novel Heartbreak Motel. This research uses a qualitative approach and content analysis method. The data source in this research is the novel Heartbreak Motel by Ika Natassa. The data in this research are in the form of quotations containing discourse context which includes background context (setting and scene), participant context (participant), result context (ends), message context (act), method context (key), means context (instrument). ), context of norms (norms), and context of type (genre) in the novel Heartbreak Motel by Ika Natassa. Data collection is obtained by reading, finding/marking, copying and grouping words that are included in the discourse context. The results of this research found 34 scenes containing eight elements of discourse context, namely background context (setting and scene) with 41 data consisting of 17 time setting data and 24 place setting data, 22 participant contexts, result contexts (ends). ) as many as 29 data, the context of the message (act) as much as 15 data, the context of the method (key) as much as 28 data, the context of the means (instrument) in which the discourse is carried out orally or directly as much as 28 data and using telephone media as much as 6 data, the context of norms ( norms) in this discourse are carried out in two directions and three directions, and the context of the type (genre) in this discourse is included in fictional prose.